Macromicroscopic Method for Vitreous Body Anatomy Studying - N. M. Kislitsyna; A. V. Shatskikh; S. M. Dibirova; D. M. Sultanova; M. P. Veselkova; S. V. Novikov (Oftalʹmologiâ, 2022)
Purpose: The vitreous body (CT), due to the complexity of its structure, remains one of the least studied anatomical structures to this day. In the literature there are attempts to describe the anatomy of the vitreous body, since the II century. The most relevant works are the studies of J. Worst et al. in 1973, in which the authors proposed new methods of CT preparation with the introduction of dyes. Despite many years of research on the structure and functions of the vitreous body and the presence of a large number of works, and there are no methods and protocols for macromicroscopic examination of the vitreous body to develop a method and propose a protocol for macromicroscopic examination of the vitreous body (VB), allowing to obtain new data on VB topographic anatomy.Materials and methods. The proposed method of macromicroscopic examination was used to study the VB topographic anatomy of 38 cadaver eyeballs. In order to color transparent structures of the vitreous, poorly soluble metallic salts (barium sulfate and copper acetate) were used. Macroscopic examination was performed using a Topcon OMS-800 operating microscope with a magnification of ×8 to ×21, microscopic changes were evaluated by light microscopy at ×50, ×100, ×200, ×400, ×630 multiple magnification with Leica DM LB2 microscope followed by photographic recording. The algorithm for macroscopic examination performing.Results and discussion. The result of macroscopic preparation was the compilation of individual anatomical and topographic maps of patients. A distinctive feature of the developed method is the ability to dissect any VB structure and to isolate each cortical layer with the possibility of studying its anatomical and topographic features and relationships with underlying tissues (internal limiting membrane, ciliary body, lens capsule). In addition, the method allows to maintain the shape and integrity of the specimens after passing through all stages of histological processing. In order to fixate VB samples, we used a method with fixing VB structures on a special adhesive-metric tablet, and placing them in a biopsy bag placed in a biopsy cassette. After that, filled in formalin, the specimens were delivered to the laboratory, where all the stages of standard processing took place.Conclusion. The developed technique of macromicroscopic examination of the vitreous allows to create an individual map of the VB topographic anatomy. After collecting of sufficient material and its statistical processing, it is possible to provide maps of the VB topographic anatomy in normal, age-related and pathological conditions.